2015
DOI: 10.1039/c5gc00062a
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of Ni-based catalysts derived from hydrotalcite for selective hydrogenation of 5-hydroxymethylfurfural

Abstract: ARTICLE This journal isSelective hydrogenation of 5-hydroxymethylfurfural (HMF) is of great importance for future energy and chemical supply. Herein, we propose for the first time that non-noble Ni-Al 2 O 3 catalysts derived from hydrotalcite-like compounds can efficiently and selectively convert HMF to 2,5-dimethylfuran (DMF), 2,5-dimethyltetrahydrofuran (DMTHF) and 2,5dihydroxymethyltetrahydrofuran (DHMTHF). Homogeneous elemental distributions of hydrotalcite-like precursor facilitate the good dispersion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
168
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(169 citation statements)
references
References 58 publications
(119 reference statements)
1
168
0
Order By: Relevance
“…It is quite well known that characteristics of the support play an important role in determining the catalytic activity of materials [20]. Noble metals such as Pd, Pt, and Ru supported on carbon prove to be excellent catalysts for hydrogenation of biomass-derived chemicals [21][22][23][24]. The main shortcoming of this material is leaching of metal nanoparticles during catalysis, which is mostly due to less interfacial interaction between the support and the metal nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…It is quite well known that characteristics of the support play an important role in determining the catalytic activity of materials [20]. Noble metals such as Pd, Pt, and Ru supported on carbon prove to be excellent catalysts for hydrogenation of biomass-derived chemicals [21][22][23][24]. The main shortcoming of this material is leaching of metal nanoparticles during catalysis, which is mostly due to less interfacial interaction between the support and the metal nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…13 For DMF production, Dumesic et al 7 reported for the first time a Ru-Cu catalyst with a yield of 76-79%. 18) and Ni-W 2 C/AC 19 ) catalysts emerged for DMF synthesis; on the other hand, they were difficult to be employed in DHMF synthesis due to the strong CC hydrogenation ability of Ni. However, few reports on the development of non-noble substitutes existed, due to their low reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among various processes explored for biomass transformation, dehydration of carbohydrates, an important type of biomass, to produce 5-hydroxymethylfurfural (HMF) is one of the most successful routes. [6][7][8][9] As one of the top building block compounds obtained from biomass, 10 HMF can be transformed into many kinds of value-added compounds and materials, [11][12][13][14] which are currently produced mainly from petroleum.…”
Section: Introductionmentioning
confidence: 99%